BEHAVIOUR OF STONE FACADES IN URBAN CENTERS INNOVATIVE BUILDING TECHNOLOGIES - Antonio Monaco (Rudarsko-geološko-naftni Zbornik, 1990)
An innovative technology using stone and granite as exterior sheeting of modern steel and concrete tall buildings is presented, Granites are chosen for the indubitable superior durability in any wheather and polluted atmosfere condition. But to guarantee durability stone sheets have to be mounted in such a way as to avoid any inner irregular stress. In particular stresses from deformation of the main structure must not be trasmitted to the exterior sheeting. Moreover an all-proof wheather barrier has to be incorporated in the factory builded sheeting panel. The innovative technology allowing use of granite and stone in facing of tall buildings is here presented along with two very important realisations: The North Tower in Genoa and the Canary Wharf in London.